Effect of an intense period of competition on race performance and self-reported illness in elite cross-country skiers - Svendsen, I. S.; Gleeson, M.; Haugen, T. A.; Tonnessen, E. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The aim of this study was to determine whether participating in a cross-country skiing stage race (Tour de Ski; TDS) affects subsequent illness incidence, training, and race performance. Self-reported training and illness data from 44 male and female elite cross-country skiers were included. In total, 127 years of data were collected (2-3 seasons per athlete). Illness incidence, training load, and performance in international competitions were calculated for athletes who did and did not participate in TDS. Forty-eight percent of athletes reported becoming ill during or in the days immediately after taking part in TDS vs 16% of athletes who did not participate. In both groups, illness incidence was somewhat lower for female athletes. For male athletes, race performance was significantly worse for 6 weeks following TDS vs 6 weeks before TDS. Furthermore, while female athletes who participated in TDS performed relatively better than controls in Olympics/World Championships, male athletes who participated in TDS typically performed worse in subsequent major championships. Participating in TDS appears to result in ~ 3-fold increase in risk of illness in this period. Male athletes appear more prone to illness and also see a drop in race performance following TDS, possibly linked to differences in training load before and after the event.